2014
DOI: 10.5152/tftrd.2014.21957
|View full text |Cite
|
Sign up to set email alerts
|

Acute Renal Failure and Urosepsis Secondary to Giant Bladder Stone in Patient with Spinal Injury

Abstract: Bladder stones account for 5% of all urinary system stones. They are frequently observed in old males and occur secondary to prostatic hyperplasia, neurogenic bladder, or other infravesical obstructions. Generally, bladder stones can be discharged spontaneously, while larger stones may block urination, resulting in full obstruction causing acute urinary retention. Furthermore, large bladder stones can cause unilateral or bilateral ureterohydronephrosis, while they can rarely cause renal failure. In this manusc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Similarly, there are studies in the literature reporting that bladder stones may cause spontaneous bladder perforations (19). Clinical studies performed in previous years demonstrate that complicated urinary tract infections appear to be the predisposing factor that should be considered carefully, especially in cases with neurogenic bladder (8,20). In our study, 14.8% of the patients were diagnosed with renal failure.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Similarly, there are studies in the literature reporting that bladder stones may cause spontaneous bladder perforations (19). Clinical studies performed in previous years demonstrate that complicated urinary tract infections appear to be the predisposing factor that should be considered carefully, especially in cases with neurogenic bladder (8,20). In our study, 14.8% of the patients were diagnosed with renal failure.…”
Section: Discussionsupporting
confidence: 71%
“…Nonetheless, urinary ultrasonography and computed tomography are other imaging modalities commonly used in diagnosis. However, definitive diagnosis is made by cystoscopic evaluation (8). In a series of studies including 94 cases, Singh et al reported that 96.8% of the stones were observed on direct urinary system graphy (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation